The Impact of Obesity and Consumption of a High Fat Diet on Anxiety-Like Behavior in Mice. (29th May 2020) - Van Leuven, Shelby; Carey, Amanda; Squiccimara, Laura; Pintea, Guilia
Abstract: Objectives: This study sought to measure the behavioral effects of consumption of a high-fat diet (HFD) on anxiety-like and depression-like behaviors in mice. It is hypothesized that animals consuming a HFD would exhibit more anxiety-like and depressive-like behaviors than their counterparts consuming a control diet. Methods: Thirty C57BL6 mice were separated into two groups ( n  = 15/each) and placed on either a HFD (60% from fat) or control diet (CD) (10% from fat) for four months prior to behavioral testing. Anxiogenic behavior was assessed by three behavioral measures: (1) marble burying, during which the number of marbles buried in bedding was recorded as an index of compulsive behavior, (2) light-dark exploration, in which time spent in the brightly-lit chamber was considered an index of anti-anxiety-like behavior and (3) the open field test, in which time spent in the brightly-lit center of the field was recorded as an index of anti-anxiety-like behavior. Depression-like behavior was assessed using the forced swim test, during which immobility was measured as an index of behavioral despair. Furthermore, the stress hormone corticosterone and the cytokine interleukin-6 (IL-6) were measured (in urine and cortex, respectively). Results: The mice fed HFD demonstrated more anxiety-like behaviors than the CD mice. The HFD-fed mice spent significantly less time in the brightly-lit chamber in light-dark exploration test and significantly less time in the center of the open field compared to the CD mice. The number of marbles buried was significantly correlated with weight and locomotor activity and thus, could not be attributed to anxiety. Analysis of the forced swim test did not reveal any significant differences in the time spent immobile or latency to immobility between the two diet groups. Urinary analysis of corticosterone levels showed greater levels of the stress hormone in the HFD-fed mice. There was also a significant increase in IL-6 in the cortex of the mice fed HFD. Conclusions: These data demonstrated that HFDs increased anxiety-like, but not depressive-like behaviors in mice. This anxiogenic behavior was associated with increased stress hormone and inflammation, however, further research is needed to determine if this association is also observed in humans. Funding Sources: Summer Undergraduate Research Program at Simmons (SURPASs).